ABI Technik : Zeitschrift für Automation, Bau und Technik im Archiv-, Bibliotheks- und Informationswesen (De Gruyter, 1996)
ABI Technik is the only German-language professional journal covering the fields of automation, building, and technology for archives, libraries, and the information sector. The journal focuses on current issues in library building, the use of modern information systems, and safeguarding and preserving collections. In addition, the journal regularly covers developments in the international library industry.